2017
DOI: 10.1016/j.cmet.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X Receptor Regulation of the NLRP3 Inflammasome Underlies Cholestasis-Associated Sepsis

Abstract: Cholestasis is a common complication of sepsis, and the increased plasma levels of bile acids are predictive of sepsis-associated mortality. However, the exact mechanism by which cholestasis aggravates sepsis development remains elusive. Here, we show that bile acids are danger-associated molecular patterns (DAMPs) that can activate both signal 1 and 2 of the NLRP3 inflammasome in inflammatory macrophages. Mechanistically, bile acids induce a prolonged calcium influx and activate the NLRP3 inflammasome synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
267
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(313 citation statements)
references
References 45 publications
11
267
1
Order By: Relevance
“…Inflammasome such as Nod‐like receptor pyrin domain‐containing protein 3 (NLRP3) is a cytoplasmic multiportion complex of the innate immune system (Hao et al, ) that leads to maturation and production of cytokines such as IL‐18, IL‐1β, and pyroptosis (lytic host cell death; Liu, Jing, et al, ; Luo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome such as Nod‐like receptor pyrin domain‐containing protein 3 (NLRP3) is a cytoplasmic multiportion complex of the innate immune system (Hao et al, ) that leads to maturation and production of cytokines such as IL‐18, IL‐1β, and pyroptosis (lytic host cell death; Liu, Jing, et al, ; Luo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…98 Intriguingly, a recent study reported that cholestasis aggravates sepsis, and bile acids not only potentiate NLRP3 and IL-1b expression but also stimulate NLRP3 inflammasome activation by driving a prolonged Ca 2+ influx. 3 It is noteworthy that this positive influence of bile acids is detected in a wide spectrum of macrophages but not in monocytes.…”
Section: Other Inflammatory Lipid Mediators and Inflammasome Activationmentioning
confidence: 98%
“…Recently, bile acids have been shown to play an active role in NLRP3 inflammasome activity by promoting the transcription of IL‐1 β and calcium mobilization in macrophages. For LPS‐induced sepsis, exogenous bile acid addition results in a notable shorter survival time for LPS‐treated mice, while pretreatment with cholestyramine resin, a sequestrant of bile acid, significantly decreased the serum level of IL‐1 β and reduced mortality . An earlier study reported that EP treatment blocked NF‐ κ B signalling in macrophages and decreased high‐mobility group box 1 (HMGB1) in circulation in septic mice .…”
Section: Metabolic Regulation Of Inflammasome Activation In Inflammatmentioning
confidence: 99%
“…This paper also suggests that extracellular ATP can prime the NLRP3 inflammasome through deubiquitination. A recent paper described that NLRP3 inflammasome regulates cholestasis-associated sepsis via sensing of bile acid and ATP 34. NLRC4 can discriminate between commensal bacteria and pathogens to suppress their colonization and to coordinate intestinal epithelial cell expulsion with lipid mediator and cytokine secretion 3537.…”
Section: Inflammasome Signaling Pathwaymentioning
confidence: 99%